2022
DOI: 10.1109/jstars.2022.3182030
|View full text |Cite
|
Sign up to set email alerts
|

Learning Digital Terrain Models From Point Clouds: ALS2DTM Dataset and Rasterization-Based GAN

Abstract: Despite the popularity of deep neural networks in various domains, the extraction of digital terrain models (DTMs) from airborne laser scanning (ALS) point clouds is still challenging. This might be due to the lack of dedicated large-scale annotated dataset and the data-structure discrepancy between point clouds and DTMs. To promote data-driven DTM extraction, this paper collects from open sources a large-scale dataset of ALS point clouds and corresponding DTMs with various urban, forested, and mountainous sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…The present RMSE is smaller than that reported in similar previous studies, although simple comparisons cannot be made because the error is expected to strongly depend on the target area characteristics (e.g., topography and coverage of buildings and trees) [9]. In the previous study that used cGAN to translate DSM into DTM [12], RMSE was 1.6 m for the area with an elevation histogram similar to that for Hyogo in the present study. The spatial resolution of their DSM was also similar to ours.…”
Section: Discussion and Concluding Remarkscontrasting
confidence: 78%
See 2 more Smart Citations
“…The present RMSE is smaller than that reported in similar previous studies, although simple comparisons cannot be made because the error is expected to strongly depend on the target area characteristics (e.g., topography and coverage of buildings and trees) [9]. In the previous study that used cGAN to translate DSM into DTM [12], RMSE was 1.6 m for the area with an elevation histogram similar to that for Hyogo in the present study. The spatial resolution of their DSM was also similar to ours.…”
Section: Discussion and Concluding Remarkscontrasting
confidence: 78%
“…Although RGB images, DSMs, and classification results for ground and nonground objects were used as input, the RMSE was 1.5-2 m. They concluded that the model would be trained to output the average elevation in the dataset. In recent years, an algorithm combining U-Net structure networks and dedicated pre-and post-data processing [9], as well as cGAN [12], have offered good results even with DSM-only input. The present study is consistent with those studies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelled point clouds are widely applied to train and test DL methods, both in indoor and outdoor environments. Some researchers process point clouds through a rasterization (Guiotte et al, 2020;Lê et al, 2022;Paz Mouriño et al, 2021) and voxelization (Tchapmi et al, 2017;Xu et al, 2021). In this way, advantages from well-studied Convolutional Neural Networks (CNNs) can be applied to point cloud structures.…”
Section: Related Workmentioning
confidence: 99%
“…Their findings shed light on the performance of these algorithms and their varying accuracy levels, influenced by factors, such as model resolution, ground slope, and point cloud density. In the domain of deep learning, Lê et al (2022) addressed the extraction of DTMs from ALS point clouds using a deep neural network approach named DeepTerRa. They collected a large-scale dataset of ALS point clouds and corresponding DTMs, training a deep neural network for direct DTM extraction through rasterisation techniques.…”
Section: Introductionmentioning
confidence: 99%